2020
DOI: 10.3390/s21010175
|View full text |Cite
|
Sign up to set email alerts
|

Robust Species Distribution Mapping of Crop Mixtures Using Color Images and Convolutional Neural Networks

Abstract: Crop mixtures are often beneficial in crop rotations to enhance resource utilization and yield stability. While targeted management, dependent on the local species composition, has the potential to increase the crop value, it comes at a higher expense in terms of field surveys. As fine-grained species distribution mapping of within-field variation is typically unfeasible, the potential of targeted management remains an open research area. In this work, we propose a new method for determining the biomass specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…(1) open-set classification can allow specimens, even those that are not present in training data, to be classified to the lowest possible taxonomic level (Lee et al, 2018); (2) synthetic image datasets can be generated using images of specimens with validated species-level identification (Skovsen et al, 2020) and (3) combination of data from multiple sources or sensors for specieslevel labelling and classification-for example, images may be complemented by DNA sequence data (Badirli et al, 2021).…”
Section: Automated Video Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…(1) open-set classification can allow specimens, even those that are not present in training data, to be classified to the lowest possible taxonomic level (Lee et al, 2018); (2) synthetic image datasets can be generated using images of specimens with validated species-level identification (Skovsen et al, 2020) and (3) combination of data from multiple sources or sensors for specieslevel labelling and classification-for example, images may be complemented by DNA sequence data (Badirli et al, 2021).…”
Section: Automated Video Analysismentioning
confidence: 99%
“…Specifically, even with an exceptionally large training dataset, the system will encounter unfamiliar species, including some that are inseparable within high‐resolution imagery. Three emerging approaches will help this challenge to be overcome: (1) open‐set classification can allow specimens, even those that are not present in training data, to be classified to the lowest possible taxonomic level (Lee et al, 2018 ); (2) synthetic image datasets can be generated using images of specimens with validated species‐level identification (Skovsen et al, 2020 ) and (3) combination of data from multiple sources or sensors for species‐level labelling and classification—for example, images may be complemented by DNA sequence data (Badirli et al, 2021 ).…”
Section: Combining Technologies To Fully Automate the Monitoring Of M...mentioning
confidence: 99%
“…In addition to directly predicting biomass values, there are studies that use image data to predict the relative content of a specific plant or crop, such as the percentage occupied, among other metrics [24][25][26]. Most of these studies analyze different grass contents in grasslands, for instance, Skovsen [27] and colleagues utilized convolutional neural networks to determine the biomass species composition of mixed crops from high-resolution color images. Data collection was conducted at four experimental sites over three growing seasons, and the method excelled in predicting the relative biomass content of clover (R 2 = 0.91).…”
Section: Related Work 1biomass Prediction Based On Imagesmentioning
confidence: 99%
“…Huang et al (2018) demonstrated that rice and weeds can be classified based on UAS RGB images using a CNN model, fully convolutional network (FCN) and transfer learning (Jiang and Li 2020). While the current methods are not applicable to complex fields where weeds of various species are intermingled, Skovsen et al (2021) demonstrated that CNN models can classify white clover, red clover and weed from rather complicated canopy images, using synthetic training data which is discussed in the later…”
Section: Weed Identificationmentioning
confidence: 99%